Semen characteristics and sperm morphology of pistia stratiotes linn. (araceae) protected male albino rats (wistar strain) exposed to sodium arsenite (2016)
Background: Sodium arsenite has been proven to be abundant in nature and released into the environment through human activities, including agricultural and industrial processes. The objective of our study was to investigate the sperm protective potential of Pistia stratiotes Linn. in arsenic-treated rats. Methods: The sperm protective potential of P. Stratiotes Linn. (Araceae) was carried out in arsenic-exposed rats using 24 male albino rats (225 to 228 g) aged between 14 and 16 weeks old. They were grouped into 4 (A–D), each group containing 6 rats. Group A animals were orally treated with 100 mg/kg ethanol leaf extract of P. Stratiotes Linn. daily for 14 days; group B (sodium arsenite at 2.5 mg/kg body weight; positive control); group C (P. stratiotes extract for 14 days and single dose of sodium arsenite on day 14; group D (0.1mL propylene glycol; negative control/vehicle). Results: Group B had a significantly lower (p < 0.05) percentage sperm motility (26.7 ± 6.67%) while group A had a significantly (p < 0.05) higher mean value (63.3 ± 3.33%) when compared across the groups. The sperm motility of rats in group D was significantly higher (p < 0.05) than groups B and C. This implies that P. stratiotes extract had no adverse effect on sperm motility. The presence of P. stratiotes with sodium arsenite alleviated its harmful effect on sperm motility. The mean value obtained for sperm viability, semen volume and sperm count followed a similar pattern although the difference was not significant (p > 0.05) for semen volume and the sperm count of rats across the groups. Total sperm abnormality was 10.44 and 14.27% with the sodium arsenite treated group having the highest value when compared with groups A treated with P. stratiotes extract and D treated with propylene, although the differences were not significant (p > 0.05). Conclusions: The study concluded that ethanol leaf extract of P. stratiotes has no negative effect on sperm motility, viability and morphology and also protected spermatozoa against arsenic-induced reproductive toxicity in Wistar strain albino rats. Therefore, it may play an important role in the protection of populations with chronic sodium arsenite exposure.